The crimes against the sacraments in the Norms of De delictis reservatis from 2010 - BOREK, DARIUSZ (Prawo Kanoniczne, 2012)
Pope John Paul II in the Motu Proprio Sacramentorum sanctitatis tutela on 30 April 2001 promulgated the norms concerning the gravest crimes reserved to the Congregation for the Doctrine of the Faith. Such an intervention of the Church, as the Pope explained, was required by the necessity to protect the sanctity of the sacraments, especially those of the Most Holy Sacrament and Sacrifice of the Eucharist and Sacrament of Penance, as well as the need to keep the purity of morality in regard to the sixth commandment of the Decalogue. The Church, driven by pastoral concern and keeping in mind the ultimate goal of any Church law, which should be salus animarum, intervenes to prevent any violation in such serious and delicate matter as the sacraments. The Congregation for the Doctrine of the Faith issued on 18 May 2001 a letter to the Ordinaries and Hierarchs of the Roman Catholic Church describing the new crimes reserved to the Congregation and the procedural norms to be followed in these cases. Nine years after the promulgation of De gravioribus delictis norms, the Congregation for the Doctrine of the Faith modified them, integrating and updating them in order to simplify the procedures, so that they could become more effective in solving contemporary problems. The modified norms concerning the crimes reserved to the Congregation for the Doctrine of the Faith were presented to Pope Benedict XVI who approved of them on 21 May 2010 and ordered to promulgate them. De delictis reservatis norms of 2010 consist of two parts: the first one, Normae substantiales, from article 1 to 7, and the second one including articles 8-31. The first part describes the competence of the Congregation, the crimes belonging to the delicta reservata category, and the norms concerning the prescription of actio criminalis in case of delicta reservata.The latter part defines the procedures in case of delicta reservata for which the Congregation for the Doctrine of the Faith is the Supreme Apostolic Tribunal. This article analyses only those of the crimes reserved to the Congregation for the Doctrine of the Faith which refer to the sacraments of the Eucharist, Penance and the Priestly Ordinations. It should be stated that both existing and new norms concerning delicta graviora show great concern of the Church for the protection of the sacraments. On the other hand, which seems alarming, the necessity to update the norms protecting the sacraments indicates their relatively frequent violation. For instance, the introduction of an attempt to ordain a woman to the category of delicta graviora was the consequence of the need to protect the nature and significance of priestly ordinations in the times of questioning the Church’s teaching in that matter. In the context of possible violations of dignified and valid administration of the sacraments, especially the Eucharist, penance and priestly ordinations, the knowledge and right interpretation of the Church norms promulgated to protect these sacraments seem vital.